The Role of Smallholder Pig Farmers in the Biosecurity of Pig Diseases in the Eastern Cape Province of South Africa - Vincent Simbizi; Rebone Moerane; Bruce Gummow (Veterinary Medicine International)
Biosecurity forms an important component of preventing disease transmission. However, data on the demographics and practices of smallholder pig farmers in Southern Africa are scant, and little is published on the biosecurity related to these farms. A questionnaire survey was, therefore, carried out in the Eastern Cape Province of South Africa to describe the demographics and practices of smallholder pig farmers and to understand their role in the biosecurity and prevention of pig diseases. Females represented 52% of pig farmers and reflect the cultural importance of pig farming in Xhosa culture. All the farmers who were interviewed had poor biosecurity measures on their farms. A low level of education, lack of training and reliance on remedies to treat and prevent pig diseases were key findings for the majority of farmers. Farmers had a poor knowledge of correct antibiotic use, which could contribute to antimicrobial resistance (AMR). Smallholder farms were found to frequently involve free-ranging pigs, swill feeding and informal trading, practices known to contribute to the spread of communicable pig diseases such as foot and mouth disease and African swine fever. Smallholder pig farms are, therefore, a potential risk for disease incursion and spread of communicable diseases within a region. Cost-effective biosecurity measures and marketing opportunities will help to prevent pig diseases, while a continuing education programme will modernise the rural pig industry and reduce the impact of AMR.